PENGARUH PENGANGGARAN PARTISIPATIF PADA SENJANGAN ANGGARAN DENGAN KETIDAKPASTIAN LINGKUNGAN DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL PEMODERASI - Tri Lestari, Ni Komang; DwijaPutri, IGAM Asri (E-Jurnal Akuntansi, 2015)
This study aims to determine the "Effects of Participative Budget on budgetary slack with Environmental Uncertainty and Organizational Commitment as moderating variables (Case Study on PT (Persero) Varuna Tirta Prakasya). This study was conducted in all branches of PT (Persero) Varuna Tirta Prakasya located in Indonesia. Sampling technique used is stratified random sampling. Data collection methods used were questionnaire and interview methods. The results showed a significant positive effect of participative budgeting on budgetary slack. Environmental uncertainty is not able to moderate the relationship between participative budgeting on budgetary slack, and organizational commitment are able to moderate the relationship between participative budgeting on budgetary slack.
Keywords: budgetary slack, participatory budgets, environmental uncertainty, organizational commitment.